Maniac Magee - Spinelli, Jerry (New York Little, Brown and Company, 1990)
After his parents die, Jeffrey Lionel Magee's life becomes legendary, as he accomplishes athletic and other feats which awe and inspire everyone around him.
Keywords: Orphans -- Fiction; Sports -- Fiction; Heroes -- Fiction; Running -- Fiction